(untitled) (Research, Society and Development, 2020)
The objective of the work is to evaluate the waste management within two companies in the clothing sector, in the city of Belém, state of Pará, Northern Brazil. Through the concept of Circular Economy, which aims to increase the useful life of the product, reusing and recycling raw materials after consumption, the aim is to understand the process of generating fabric waste, as well as its collection and final destination, proposing improvements to the existing process. The information was obtained from the managers and employees of the companies, through a questionnaire and on-site observation. It was analyzed, mainly, the types of textile fibers used in the manufacture, the amount of waste produced and the management of waste, in addition to the information on the characterization of the enterprise. The results reveal that the largest company fits the EC principles, highlighting the innovation in defibrated textiles. The local company is in disagreement with the basic rules of conduct related to environmental legislation, requiring a Solid Waste Management Plan that allows the reuse of waste in order to reduce its production costs, as there is no textile recycling factory in Belém. It is concluded that the management and management of solid waste are fundamental for environmentally appropriate disposal and final disposal and, specifically, in the textile industrial sector, circularity can generate better productive efficiency.